Longevity and Recovery Rate of Indonesian Local Ram Spermatozoa in Homemade and Commercial Extenders - Kamal, Lutfhi Annisa; Agil, Muhammad; Said, Syahruddin; Nugraha, Taufiq Purna; Arifiantini, Raden Iis (Indonesian Journal of Applied Research (IJAR), 2026)
Sheep farming plays a crucial role in Indonesia's livestock industry; however, the effectiveness of artificial insemination (AI) is hindered by the less-than-ideal quality of cryopreserved semen. This research assessed the longevity and progressive motility recovery rate (RR) of frozen semen from local Indonesian rams, using a homemade Tris egg yolk (TEY) extender and three commercial extenders (AndroMed®, Steridyl®, BoviFree®). Semen from three rams (Batur, Garut, and Sakub) was processed, frozen in 0.25 mL straws (50 × 10⁶ sperm per straw), and its quality was evaluated using CASA. Longevity was monitored hourly from 0 to 4 h at 37°C. The data were analyzed using a Randomized Block Design with ANOVA, followed by Duncan’s Multiple Range Test. Sperm motility decreased over incubation time for all extenders, with notable differences at 4 h (total motility, p = 0.017; progressive motility, p = 0.023). Commercial extenders preserved higher total and progressive motility than TEY, with Steridyl® showing the highest mean RR (64.11%; mean all rams; RR analysis, n = 18), significantly outperforming Andromed®, BoviFree®, and TEY (p = 0.007). The superior results of Steridyl® align with its low-density lipoprotein content, which stabilizes the sperm membranes during cryopreservation. In summary, Steridyl® was the most effective extender for maintaining motility and RR of frozen semen from local Indonesian rams, potentially enhancing AI success in small ruminant programs.